DEVELOPMENT OF AN EXPERIMENTAL INSTALLATION WITH A BUNKER-FEEDER AND ITS DESCRIPTION - Maksad Axmedov; Akramjon Sarimsakov; Xamidulla Isaxanov (International Journal of Innovations in Engineering Research and Technology, 2024)
In the article, after the ginning process in cotton ginning enterprises, ginned seeds are analyzed. A device is recommended for extracting the seeds that have fiber that can be spun from inside them (non-ginned), and the working scheme and principle of operation of the device are presented.